Adsorption isotherm, kinetic modeling and mechanism of 2,4,6-trichlorophenol on coconut husk-based activated carbon - Ivy Tan, Ai Wei; Hameed, Bassim Hamid; Abdul Latif, Ahmad (Elsevier Ltd., 2008)
The adsorption characteristics of 2,4,6-trichlorophenol (TCP) on coconut husk-based activated carbon prepared under optimized conditions were evaluated. Batch adsorption studies were conducted to study the effects of various parameters such as initial concentration, agitation time and solution pH on TCP adsorption. Adsorption capacity was found to increase with increase in initial concentration and agitation time, while acidic pH was more favourable for the adsorption of TCP. Equilibrium data were analyzed by the Langmuir, Freundlich, Temkin and Redlich–Peterson models by using non-linear regression technique. The equilibrium data were best represented by the Langmuir isotherm, yielding maximum monolayer adsorption capacity of 716.10 mg/g at 30 °C. The adsorption kinetics was found to follow the pseudo-second-order kinetic model. The mechanism of the adsorption process was determined from the intraparticle diffusion model. Boyd plot revealed that the adsorption of TCP on the activated carbon was mainly governed by particle diffusion. Coconut husk-based activated carbon was shown to be an efficient adsorbent for removal of TCP from aqueous solutions.